Does a short Pollard walk transect capture butterfly and bee diversity? A test to inform pollinator monitoring and community science initiatives. Issue 6 (5th June 2022) - Viliani, Leonardo; Bonelli, Simona; Vercelli, Monica; Roy, David B.; Riva, Federico
Abstract: Widespread declines in insects will threaten ecosystem functioning and services. Nevertheless, a lack of data hinders assessments of population and biodiversity trends for many insect groups and thus effective conservation actions. Implementing cost‐effective, unbiased, and accurate monitoring programmes targeting different groups across a larger geographical range has therefore become a key conservation priority. We evaluated a sampling protocol designed for community science initiatives targeting butterflies and bees. Specifically, we tested how well a short (200‐m long) version of traditional Pollard walk transects, designed to be accessible for large numbers of community scientists, captures changes in alpha and beta diversity of these two pollinator groups. We used resampling methods to simulate and assess scenarios varying in sampling intensity and frequency. We found that alpha and beta diversity of butterflies and bees were estimated at similar accuracies across different scenarios, which suggests that even short transects can provide useful information on diversity patterns for both taxa. However, common sampling frequencies resulted in low accuracies (e.g. one sample every 10 days finds on average ~50% of the species present at a site). We discuss our results in the context of developing large scale, structured monitoring systems for multiple insect taxa, and how information on biodiversity patterns can inform the expansion of monitoring schemes. We explain why, moving forward, even rapid sampling designs similar to the approach tested here will be useful given a higher potential to involve community scientists, data integration techniques, and the opportunities to sample under‐represented habitat types Abstract : Implementing effective monitoring programmes targeting different taxa across large geographical ranges is a priority to understand changes in pollinator biodiversity A short version of Pollard walks can provide useful information on diversity patterns for butterflies and bees Quick sampling protocols have the potential to reduce spatial biases in monitoring, complement ongoing schemes via data integration, and facilitate community science initiatives